2020
DOI: 10.1186/s12872-020-01778-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between two different definitions of contrast-associated acute kidney injury for long-term mortality in patients with diabetes undergoing coronary angiography: a prospective cohort study

Abstract: Background The definitions of contrast-associated acute kidney injury (CA-AKI) are diverse and have different predictive effects for prognosis, which are adverse for clinical practice. Few articles have discussed the relationship between these definitions and long-term prognosis in patients with diabetes. Methods A total of 1154 diabetic patients who were undergoing coronary angiography (CAG) were included in this study. Two definitions of CA-AKI were used: CA-AKIA was defined as an increase ≥ 0.3 mg/dl or &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…For example, Centola et al investigated 402 ST-segment elevation MI (STEMI) patients who underwent primary PCI and detected a remarkable correlation between mortality and CA-AKI when applying the ESUR and AKIN definitions during a median 1-year followup period (27); in addition, the AKIN classification achieved better prognostic accuracy than the ESUR criteria (area under the receiver operating curve; 0.7984 vs. 0.7759; p = 0.0331). Similarly, Lun et al showed that both the ESUR and AKIN definitions were associated with long-term mortality (28). However, it is noteworthy that the population attributable risk (PAR) for the AKIN definition was greater, thus indicating that this definition exhibited higher clinical relevance than the ESUR definition.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Centola et al investigated 402 ST-segment elevation MI (STEMI) patients who underwent primary PCI and detected a remarkable correlation between mortality and CA-AKI when applying the ESUR and AKIN definitions during a median 1-year followup period (27); in addition, the AKIN classification achieved better prognostic accuracy than the ESUR criteria (area under the receiver operating curve; 0.7984 vs. 0.7759; p = 0.0331). Similarly, Lun et al showed that both the ESUR and AKIN definitions were associated with long-term mortality (28). However, it is noteworthy that the population attributable risk (PAR) for the AKIN definition was greater, thus indicating that this definition exhibited higher clinical relevance than the ESUR definition.…”
Section: Discussionmentioning
confidence: 97%
“…The traditional scoring system using the NCDR-AKI risk model is an effective in estimating the risk of AKI after PCI 9 , 10 . We used the definition of AKI as serum creatinine by ≥ 0.3 mg/dl or an increase to ≥ 50% since this definition is the most optimal to predict short-term and long-term adverse mortality as well as the NCDR-AKI risk model 9 , 12 , 30 , 31 . Additionally, we did not include contrast volume according to the NCDR-AKI risk model because the causes of AKI are multifactorial such as contrast or hemodynamically instability and pre-operative assessment the risk of AKI is paramount to decrease the amount of contrast volume.…”
Section: Discussionmentioning
confidence: 99%
“…13 Compared to the 28% rate of CA-AKI among patients with DM in the present study, another recent study found a rate of 37% in patients with DM undergoing percutaneous coronary interventions (PCI) using the same definition of CA-AKI as in the present study, but the amount of iodinated contrast media administered was not stated. 14 There might be several reasons for the lower doses of administered iodine contrast media in patients with DM than those without DM during thrombolysis. The occlusive lesions may be more distal in patients with DM, even if this could not be convincingly shown in the present study, necessitating less accurate angiographic imaging of the aorto-iliac segment and therefore less need of contrast media.…”
Section: Discussionmentioning
confidence: 99%
“…13 Compared to the 28% rate of CA-AKI among patients with DM in the present study, another recent study found a rate of 37% in patients with DM undergoing percutaneous coronary interventions (PCI) using the same definition of CA-AKI as in the present study, but the amount of iodinated contrast media administered was not stated. 14…”
Section: Discussionmentioning
confidence: 99%